2013
DOI: 10.5114/pwki.2013.34036
|View full text |Cite
|
Sign up to set email alerts
|

Transient cortical blindness after coronary artery angiography

Abstract: Coronary angiography is the current gold standard for the diagnosis of ischemic heart disease and therefore the prevalence of percutaneous coronary procedures such as angiography and angioplasty is high. The occurrence of cerebral complications after coronary angiography and coronary angioplasty is low and it mainly includes transient ischemic attack and stroke. The prevalence of transient cortical blindness after X-ray contrast media is low and it is usually seen after cerebral angiography. Until now only a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…From the search results, we identified five case series and 38 case reports , for a total of 52 patients. The first published report documenting presumed CIE associated with cardiac catheterization dates from 1970 .…”
Section: Resultsmentioning
confidence: 99%
“…From the search results, we identified five case series and 38 case reports , for a total of 52 patients. The first published report documenting presumed CIE associated with cardiac catheterization dates from 1970 .…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have demonstrated that contrast agents may induce vasodilation, shrinkage of cerebrovascular endothelial cells, and widened endothelial tight junctions (1315). Moreover, previous studies found that the risk of transient cortical blindness increases when the contrast agent in the cerebral circulation is higher (9, 16). A higher dose of contrast agent could prolong the duration of exposure of the cerebrovascular endothelium to the contrast agent by increasing the transit time, thus resulting in blood–brain barrier breakdown, which would further increase the transfer of contrast material (17).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, cortical blindness and transient cortical blindness have also been reported which developed after coronary angiography intervention or cardiopulmonary resuscitation [6,7]. What distinguished our case from other cases is that the onset of the stroke affected the right visual field a year ago and newly developed stroke affected the left visual field which resulted in cortical bilateral total vision loss.…”
Section: Discussionmentioning
confidence: 60%